Analisis Faktor-Faktor yang Mempengaruhi Minat Pemanfaatan Teknologi Informasi bagi Auditor - Dian Puji Puspita Sari; Arief Rahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The era of modernization nowadays, humans are very dependent on technology. This makes technology become a basic need for everyone. This study aims to analyze the factors that influence the interest in using information technology for auditors in Yogyakarta. Independent variables used include performance expectations, business expectations, social factors, conditions that facilitate and suitability of tasks. Respondents in this study were auditors who used IT in their work. The number of respondents was 106 respondents. The data analysis method used is structural Equation Model (SEM) using Partial Least Square (PLS) software. The results of this study state that performance expectations, business expectations, social factors, facilitating conditions and suitability of tasks have a positive effect on the interest in using information technology for auditors in Yogyakarta. Keywords: Interest, Information Technology, Auditor